Initial Recognition Results of Species Composition and Characteristics of Harmful Organisms at My Son Sanctuary Heritage Area - Huy, Nguyen Quoc (VNU Journal of Science: Natural Sciences and Technology, 2017)
The results of the three-year survey (2012-2014) on composition of pest species of the My Son Sanctuary recorded 50 species, including 16 termite species(invertebrates), 9 vertebrates species, 5 fungals genera and 16 plant species. Of these, only one termite species invaded directly the towers but the damage level caused by it was lightly . Three genera of fungi (Aspergillus, Trichoderma and Penicillium) were identified as major damage species to the towers. The most dangerous level from these fungi was determined in the towers C, B, followed  in the tower D and tower A. Among six plant species found to damage the My Son Towers, four species wereinvading to all of towers: Bidens pilosa L., Tectaria zeylanica (Houtt.) Sledge, Hedyotis diffusa Willd, and Selphinella delicatula (Desv.) Alston). There were 6/9 vertebrates species (66.67%) having harmful effectiveness to the towers but with light level. Overall review about harmful impacts of pests for researched relics identified the main pests  for whichthe control solutions need to be counted in the My Son Sanctuary, such as Bidens pilosa L., Tectaria zeylanica (Houtt.) Sledge, Hedyotis diffusa Willd and Selphinella delicatula (Desv.) Alston).